2005
DOI: 10.1002/mrc.1634
|View full text |Cite
|
Sign up to set email alerts
|

HPLC–NMR for tissue‐specific analysis of phenylphenalenone‐related compounds in Xiphidium caeruleum (Haemodoraceae)

Abstract: HPLC-(1)H NMR has been used to study the tissue-specific distribution of phenylphenalenones, polyphenolic natural products of Xiphidium caeruleum, a neotropical member of the Haemodoraceae plant family. The present results provide insight into the occurrence of phenylphenalenone-related compounds in root segments of whole plants and different in vitro culture lines of the same species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
(18 reference statements)
1
7
0
Order By: Relevance
“…Fifteen micrograms (∼52 nmol) of oxypeucedanin (22 μg of oxypeucedanin hydrate, ∼72 nmol) in the 1.5 μL detection cell were sufficient to obtain an unambiguous 1 H NMR spectrum in about 2 min 20 s. This technique reduces the required sample quantity by a factor of up to 15 in comparison to a 5 mm tube in a conventional commercial probe. It is for this reason that the microcoil 1 H NMR technique proves useful with mass-limited samples and as a detector in capillary separations, as often demonstrated by our group [27][28][29][30] and several other very active European groups [31][32][33][34][35][36]. Moreover, our results confirmed that disk diffusion is a reliable, easy and inexpensive semi-quantitative susceptibility testing method that is sufficiently sensitive and ideally suited for preliminary investigations on the nano-to microscale.…”
Section: Resultssupporting
confidence: 80%
“…Fifteen micrograms (∼52 nmol) of oxypeucedanin (22 μg of oxypeucedanin hydrate, ∼72 nmol) in the 1.5 μL detection cell were sufficient to obtain an unambiguous 1 H NMR spectrum in about 2 min 20 s. This technique reduces the required sample quantity by a factor of up to 15 in comparison to a 5 mm tube in a conventional commercial probe. It is for this reason that the microcoil 1 H NMR technique proves useful with mass-limited samples and as a detector in capillary separations, as often demonstrated by our group [27][28][29][30] and several other very active European groups [31][32][33][34][35][36]. Moreover, our results confirmed that disk diffusion is a reliable, easy and inexpensive semi-quantitative susceptibility testing method that is sufficiently sensitive and ideally suited for preliminary investigations on the nano-to microscale.…”
Section: Resultssupporting
confidence: 80%
“…The function of these polycyclic aromatic natural products in plant defense suggests formation and/or storage in speciWc cells or tissue. In Xiphidium caeruleum (Haemodoraceae), tissue-and cell-speciWc localization of phenylphenalenone-related compounds and their glucosides was studied by confocal laser-scanning microscopy, microspectral photometry, and high-performance liquid chromatography coupled to NMR spectroscopy in Opitz et al (2003) and Schneider et al (2005). Previous microscopical investigations of leaves of Dilatris pillansii revealed crimson-colored secretory cavities (SC) (Schulze 1893).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many other studies have found evidence of this nature in different plants, where 9-PhPN is present. 14−16 To confirm their protective function, Schneider et al 17,18 measured the amount of 9-PhPN in various parts of the plants (roots, leaves, stems, ...) of different ages and concluded that the roots contained the highest concentration and mostly in younger areas. The same distribution was known to be followed by other compounds of proven phytoalexin properties, and therefore, 9-PhPN was labeled as such.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the 1970s Cooke detected the presence of 9-PhPN compounds in some plant species. , However, the function of these compounds was not clear until Luis et al and Binks uncovered a probable relationship between 9-PhPN and phytoanticipin properties. Since then, many other studies have found evidence of this nature in different plants, where 9-PhPN is present. To confirm their protective function, Schneider et al. , measured the amount of 9-PhPN in various parts of the plants (roots, leaves, stems, ...) of different ages and concluded that the roots contained the highest concentration and mostly in younger areas. The same distribution was known to be followed by other compounds of proven phytoalexin properties, and therefore, 9-PhPN was labeled as such. , …”
Section: Introductionmentioning
confidence: 99%